Evaluasi Maturity Manajemen Investasi Pada Dinas Komunikasi, Informatika, Statistik Dan Persandian Provinsi Banten Menggunakan Framework Information Technology Investment Management - Zulfa Fahimah; Himawat Aryadita; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Dinas Komunikasi Informatika Statistik dan Persandian (DISKOMINFO) Banten Province performs the functions and authority of the management of information and public communication one of them is the management of e-Government. E-Government is the use of technology that connects government institutions with other parties. DISKOMINFO contemplate an action to which investment management has been implemented to support the function and authority as well as recommendations to the investment management to be considered for future improvement. Evaluating investment management based on the Information Technology Investment Management (ITIM) framework using interviews, observations and documentation studies. From the calculation results, the maturity level of investment management at DISKOMINFO is in maturity stage 1 which is investment management that is applies had characterized ad hoc, unstructured and unpredictable . Some recommendations are given to each key process that be able to rise to the next stage of maturity some of them is the form of documentation planning starting from requirement, schedule planning and also the risks that can occur.